Neutrosophic gb-closed Sets and Neutrosophic gb-Continuity - C.Maheswari (Neutrosophic Sets and Systems, 2019)
Smarandache introduced and developed the new concept of Neutrosophic set from the Intuitionistic fuzzy sets. A.A. Salama introduced Neutrosophic topological spaces by using the Neutrosophic crisp sets. Aim of this paper is we introduce and study the concepts Neutrosophic generalized b closed sets and Neutrosophic generalized b continuity in Neutrosophic topological spaces and its Properties are discussed details.